Model and Practice of Strategic Policy Process in Indonesia: Case Study Strategic Management in Indonesian Central Government (2009-2012) - Achmad Nurmandi (Sciedu Press, 2012)
Since 1998, the Indonesian government had introduced an approach for Strategic Management under Government Regulation No. 108/200 the government has not evaluated experiences with this strategy. However, in 2009, the administration of President Yudhoyono introduced a new approach entitled Rencana Pembangunan Jangka Menengah (RPJMD) –Medium Term Development Planning. The interesting question regards the compliance of government with this strategic plan. In other words, is the implementation of the strategic plan proceeding? In this paper, both writers investigate experiences with the attempt to introduce the model and practice of Strategic Management in the Indonesian public sector, particularly the aspects of process and tools. The Research method used in this research is historical and descriptive using the casual loop model of system dynamics method. The study found that the model of strategic planning applied by the government was a linear process model a linked to key success factors of leadership, professional coordination among governmental units, and monitoring of the complete process and its instruments: planning, implementation and evaluation.